Physical Work Environment, Sick Building Syndrome and Mental Health of Factory Workers - Malik, Urooj; Qayyum, Dr Shazia; Fatima, Dr Iram (The journal of contemporary issues in business and government, 2021)
The current study is aimed at exploring the relationship between physical work environment, sick building syndrome and mental health of factory workers. Sample of the study consisted of (N =300) men and women factory workers by using purposive sampling technique. It was hypothesized that there will likely to be a relationship between physical work environment, sick building syndrome and mental health of factory workers, Physical work environment will likely to be a predictor of mental health. Further it was hypothesized that Sick building syndrome will be a mediator between physical work environment, and mental health of factory workers. Other hypothesis was that Female will likely to be higher on physical work environment, sick building syndrome and mental health than males. Descriptive statistics were calculated to assess means, standard deviations and frequencies of the variables. Pearson product moment correlation was used to find out relationship among work environment, sick building syndrome and mental health and hierarchical regression was used for prediction. The mediating role of variables was assessing through Process Macro. Independent sample t test was used to analyses the gender differences among study variables. Physical Work Environment Scale (PWES) (Erikson, 1999), Sick building Syndrome Survey Questionnaire (SBSSQ) (Israeli & Pardo, 2011), and Subjective well-being Scale (SWBS) (Stone & Christopher, 2013) were used for assessment. The result indicated that Physical Work environment had a negative relationship with sick building syndrome and mental health of factory workers. Indoor air quality had a negative relationship with mental health of factory workers. All the other dimensions of physical work environment (Lighting, ergonomics and acoustics) had a positive relationship with mental health of factory workers. Physical Work environment had a positive predictor of mental health of factory workers. Sick building syndrome had a negative predictor of mental health of factory workers. Demographic variables (age, gender, family system, number of children, region) were predictor of mental health. Sick building syndrome had a mediator between physical work environment and mental health of factory workers. Sick building syndrome had a mediator between dimension of physical work environment (indoor air quality, ergonomics and lighting) and mental health of factory workers. Females were high on physical work environment, sick building syndrome and mental health than male. This research can provide help for managers understanding multi dimensions of environment of work and impact of dimensions on employee for job satisfaction. This research can also understand the work environment of employees. It helps organizations to create effective work environment.